Repeatability and Comparability of Retinal Blood Vessel Caliber Measurements by OCTA - Joby Tsai; Samuel Asanad; Martha Whiting; Xuemin Zhang; Laurence Magder; Osamah Saeedi (Vision, 2023)
Background: To investigate the repeatability in vessel caliber measurements by optical coherence tomography angiography (OCTA). Methods: In this prospective study, 28 patients (47 eyes) underwent sequential OCTA imaging of the optic nerve head and macula. Two independent masked graders measured vessel caliber for sequential images of the optic nerve head and macula. The average vessel width was determined and variability between graders and images. Results: A total of 8400 measurements of 420 vessels from 84 OCTA images were included in the analysis. Overall, inter-grader agreement was excellent (ICC 0.90). The coefficient of variation (CoV) for all repeated OCTA images was 0.10. Greater glaucoma severity, older age, macular location, and diagnosis of diabetes were associated with thinner vessels (p < 0.05). CoV was higher in the peripapillary region (0.07) as compared to the macula (0.15). ICC was high for all subgroups except for the macula (ICC = 0.72). Conclusions: Overall, the repeatability of vessel caliber measurements by OCTA was high and variability low. There was greater variability in the measurement of macular vessels, possibly due to technical limitations in acquiring accurate vessel widths for smaller macular vessels.